Training in art - Anish, Blanche L., artist (Ohio : Federal Art Project, WPA, 1937)
Poster announcing training opportunities in art in such areas as decorator, art teacher, photographer, stylist sculptor, mural painter, window trimmer, portrait painter, interior decorator, landscape architect, and theater art director.